Stranger Things: Science Camp #4 #4 / Science camp. - Houser, Jody; Salazar, Edgar, 1973-; Champagne, Keith; Louise, Marissa; Piekos, Nate (Minneapolis, Minnesota : Spotlight, 2022)
The science-focused summer camp Dustin is attending has been besieged by a sinister figure wearing a menacing Einstein mask. While the camp counselors themselves debate what to do to keep the kids safe, Dustin and Suzie round up a crew of kids to get to the bottom of the mystery and protect themselves!
Keywords: Disappearances (Parapsychology) -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Camps -- Comic books, strips, etc; Disappearances (Parapsychology) -- Fiction; Monsters -- Fiction; Camps -- Fiction; Horror comics; Science fiction comics; Science fiction comics; Horror comics; Graphic novels